Grip strength as a systems biomarker of aging: neuromuscular junction constraints and biomarker decoupling in gene therapy - Patrick E. Sewell; Christopher Jensen (Frontiers in Aging, 2026)
Grip strength has emerged as one of the most robust predictors of mortality, disability and healthspan across populations. Yet its predictive validity rests on an often-unstated assumption: that grip strength serves as a passive readout of systemic biological integrity rather than an isolated measure of forearm function. Here we propose that grip strength derives its prognostic power from its position as a convergent output of multiple aging-sensitive physiological systems—including neuromuscular, vascular, metabolic, endocrine and inflammatory networks. We highlight the neuromuscular junction (NMJ) as a particularly critical and often-overlooked rate-limiting factor, noting that age-related strength loss (∼2.5–4% annually) outpaces mass loss (∼0.6–1% annually) by two-to fivefold—a disparity attributable in large part to NMJ deterioration. We introduce the concept of biomarker decoupling and apply it to the emerging landscape of longevity gene therapies being explored in early translational and compassionate-use settings—including follistatin, klotho, FOXO3, hTERT, SIRT1, PGC-1α, VEGF and FGF21. Critically, we argue that follistatin’s anabolic efficacy is contingent on intact NMJ integrity, with denervated muscle fibers exhibiting a blunted net anabolic response despite elevated follistatin expression—creating a therapeutic paradox wherein mass gains can occur without proportional functional improvement. We provide a conceptual analysis of how each therapy may influence grip strength, predict decoupling risk based on the breadth of systems affected, outline plausible timing windows for intervention, and propose a heuristic framework for clinical interpretation. The decoupling categories and any numeric ranges presented here are conceptual and hypothesis-generating rather than empirically validated.